2006
DOI: 10.1073/pnas.0509892103
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Perutz's double-β-stranded subunit structure for β-amyloids also applies to their channel-forming structures in membranes

Abstract: Although there is a growing body of evidence that different amyloidoses may have a similar molecular mechanism in common, the many details of this mechanism are not understood. In this study, we propose that there is a common molecular structure of the primary agents of these diseases, namely a small oligomer of Perutz's cylindrical double-␤-stranded subunit for polyglutamine and that this structure, which contains a central water-filled core, can spontaneously integrate into the bilayers of membranes to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 22 publications
(14 reference statements)
0
38
2
Order By: Relevance
“…However, it is hard to compare the two experimental paradigms. Indeed, it has been demonstrated that Aβ peptides with less than 40 amino acids which do not form conducting pores in black lipid bilayer films and in intact cell membranes, are not neurotoxic in cultured hippocampal neurons [44]. Thus, it is possible that the discrepancy with our data is due the different form of Aβ utilized.…”
Section: Discussioncontrasting
confidence: 75%
“…However, it is hard to compare the two experimental paradigms. Indeed, it has been demonstrated that Aβ peptides with less than 40 amino acids which do not form conducting pores in black lipid bilayer films and in intact cell membranes, are not neurotoxic in cultured hippocampal neurons [44]. Thus, it is possible that the discrepancy with our data is due the different form of Aβ utilized.…”
Section: Discussioncontrasting
confidence: 75%
“…At present, it is hard to find an explanation for this result. Recently, Singer and Dewji (2006) proposed that the common molecular structure responsible for the toxicity of the early oligomeric aggregates of amyloidogenic proteins and peptides is the cylindrically wound double-b-stranded subunit that Perutz et al (2002) derived from the X-ray diffraction studies of polyglutamine fibers. This structure interacts with cell membrane, forming a water-filled channel of about 15 nm in diameter, large enough to permit the diffusion of small ions.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the number of patients needed would be much greater. Sickle erythrocytes were studied in relation to amyloid only [41,42] , but theoretically their increase could be detected in many other diseases. Therefore, to draw correct clinical conclusions, more studies will have to be conducted in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes bind amyloid dimers or trimers [41,42] that generate pore-like structures on the erythrocyte membrane and can alter the cell membrane and volume. They exhibit ionophore-like properties [43] and undergo OS, resulting in an increase in erythrocyte size and the assumption of an elongated shape (sickle erythrocytes).…”
Section: Introductionmentioning
confidence: 99%